PERSEPSI SISWA REGULER TERHADAP SOSIALISASI SISWA TUNARUNGU - Ebid Lendra (Jurnal Penelitian Pendidikan Khusus, 2012)
This research background by differing perceptions / perspectives grade students VII.2 Regular SMPN 23 Padang on Deaf student socialization classes SMP VII.2 Padang. The purpose of this study was to describe how students' perceptions of the socialization of students' regular classroom Deaf Padang VII.2 in SMP 23, reviewed in the areas of social interaction, communication and cooperation with the Deaf students' entire academic SMPN 23 Padang, both in the classroom, outside classroom and in extracurricular activities in SMP 23 Padang. The methods used in this research is descriptive quantitative approach. The sampling technique is the total sampling, in which all regular students of VII. 2 SMP 23, amounting to 36 people.